Perilaku Etis Mahasiswa Akuntansi Ditinjau Dari Locus of Control dan Love of Money: Ethical Behavior of Accounting Students From Locus of Control and Love of Money - Dewi , Ni Nyoman Sri Rahayu Trisna (Journal of Accounting Science, 2019)
Ethical behavior is related to self-control. A person who is able to control himself will not easily carry out unethical actions intentionally. Ethical violations committed by someone can also be based on a factor of money. Someone who to love with money will tend to do various ways to meet their needs, even though they deviate from ethical behavior. This study aimed at determine the effect of locus of control and love of money on the ethical behavior of accounting students at the Faculty of Business, Triatma Mulya University. This study used a saturated sampling method, so that the number of samples obtained is 38 students. The analysis technique used in this research was multiple regression analysis. The results showed that locus of control had a positive effect on the ethical behavior of the accounting students of the Faculty of Business, Triatma Mulya University, while love of money had no effect on the ethical behavior of accounting students at the Faculty of Business, Triatma Mulya University.